2003
DOI: 10.1256/qj.01.212
|View full text |Cite
|
Sign up to set email alerts
|

Orographic precipitation and air mass transformation: An Alpine example

Abstract: SUMMARYA case of orographic precipitation in the Alps on 20 September 1999 was studied using several models, along with rain-gauge and radar data. The objective of the study is to describe the orographic transformation of an air mass, including multi-scale aspects. Several new and some conventional diagnostic quantities are estimated, including drying ratio, precipitation ef ciency, buoyancy work, condensed-water residence time, parcel changes in heat, moisture and altitude, and dominant space-and time-scales.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 38 publications
4
102
0
Order By: Relevance
“…Besides the above-mentioned deficiency in the cloud microphysical scheme (Smith et al, 2003), the freeatmosphere temperature and wind fields were found to be heavily disturbed by grid-scale numerical noise over the Alps despite heavy smoothing of the model topography. Schär et al (2002) suggested that numerical errors related to the terrain-following coordinate system (Gal-Chen and Somerville, 1975) were responsible for these undesirable noisy structures.…”
Section: Model Improvements Triggered By Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the above-mentioned deficiency in the cloud microphysical scheme (Smith et al, 2003), the freeatmosphere temperature and wind fields were found to be heavily disturbed by grid-scale numerical noise over the Alps despite heavy smoothing of the model topography. Schär et al (2002) suggested that numerical errors related to the terrain-following coordinate system (Gal-Chen and Somerville, 1975) were responsible for these undesirable noisy structures.…”
Section: Model Improvements Triggered By Mapmentioning
confidence: 99%
“…Benoit et al (2002) show that the MC2 real-time forecasts captured the timing and the structure of the precipitation events quite well but underpredicted the magnitude of the precipitation by a factor of 2. The systematic underprediction was subsequently attributed to an error in the cloud microphysical scheme, leading to an excessive residence time of cloud water in the model (Smith et al, 2003). Unfortunately, due to the early development stage of the MC2, no final conclusion could be drawn regarding the merit of high-resolution models that work without parametrization for cumulus convection.…”
Section: Studies Covering the Entire Sopmentioning
confidence: 99%
“…However, a change in precipitation efficiency could also lead to a change in precipitation amounts. Smith et al (2003) found that precipitation efficiency can lead to artificially inflated condensation rates over multiple ridges. To evaluate how efficient Langfjella generates precipitation, the drying ratio (DR, the fraction of incoming water vapor flux that is rained out as air passes over the terrain) was examined.…”
Section: Area Averaged Responsementioning
confidence: 99%
“…Rain-gauge networks are typically not dense enough to reproduce such high spatial variability; even in the European Alps, one of the regions with the densest rain-gauge network, typical spacing between stations is 10 km, whereas the precipitation distribution varies at scales smaller than 10 km (e.g. Frei and Schär, 1998;Smith et al, 2003). Ground-based radars, on the other hand, are designed to monitor precipitation over large areas with high spatial and temporal resolution.…”
Section: The Challenge Of Nowcasting Orographic Precipitationmentioning
confidence: 99%